PerSurge (NOA-30) phase II trial of perampanel treatment around surgery in patients with progressive glioblastoma - Heuer, Sophie; Burghaus, Ina; Gose, Maria; Keßler, Tobias; Sahm, Felix; Vollmuth, Philipp; Venkataramani, Varun; Hoffmann, Dirk C.; Schlesner, Matthias; Ratliff, Miriam; Hopf, Carsten; Herrlinger, Ulrich; et al. (BMC cancer, 2024)
Glioblastoma is the most frequent and a particularly malignant primary brain tumor with no efficacy-proven standard therapy for recurrence. It has recently been discovered that excitatory synapses of the AMPA-receptor subtype form between non-malignant brain neurons and tumor cells. This neuron-tumor network connectivity contributed to glioma progression and could be efficiently targeted with the EMA/FDA approved antiepileptic AMPA receptor inhibitor perampanel in preclinical studies. The PerSurge trial was designed to test the clinical potential of perampanel to reduce tumor cell network connectivity and tumor growth with an extended window-of-opportunity concept.
Gesehen am 17.01.2024